DNA-based electrochemical nanobiosensor for the detection of Phytophthora palmivora (Butler) Butler, causing black pod rot in cacao (Theobroma cacao L.) pods. (August 2019) - Franco, Anthony James DM.; Merca, Florinia E.; Rodriguez, Myrna S.; Balidion, Johnny F.; Migo, Veronica P.; Amalin, Divina M.; Alocilja, Evangelyn C.; Fernando, Lilia M.
Abstract: A nanobiosensor was developed for the electrochemical detection of Phytophthora palmivora, a notorious pathogen of cacao causing severe crop loss. Sandwich hybrids between two oligonucleotide probes and the genomic DNA of P. palmivora were prepared and electrochemically detected. The oligonucleotide probes were designed based on the ITS sequence of the P. palmivora field isolates. The detection of sandwich hybrids with P. palmivora genomic DNA and the selectivity of the nanobiosensor towards it compared to other cacao-associated fungal pathogens were demonstrated. The detection limit was determined to be at 0.30 ng DNA μL −1 . Detection of P. palmivora DNA on cacao samples was also demonstrated. The result of the preliminary analysis on cacao pod samples shows the potential of the developed nanobiosensor for reliable and more cost-effective analysis of field samples. Highlights: Oligonucleotide probes were designed based on the ITS sequence of P. palmivora . The electrochemical detection scheme was confirmed to work in the presence of P. palmivora genomic DNA. The selectivity of detection assay was demonstrated, and the detection was found to be sensitive down to 0.30 ng DNA μL-1. Detection trials in pods showed successful results and discrimination of symptoms caused by P. palmivora from other pathogens.